If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30t + 1 = t Reorder the terms: 1 + 30t = t Solving 1 + 30t = t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 1 + 30t + -1t = t + -1t Combine like terms: 30t + -1t = 29t 1 + 29t = t + -1t Combine like terms: t + -1t = 0 1 + 29t = 0 Add '-1' to each side of the equation. 1 + -1 + 29t = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 29t = 0 + -1 29t = 0 + -1 Combine like terms: 0 + -1 = -1 29t = -1 Divide each side by '29'. t = -0.03448275862 Simplifying t = -0.03448275862
| q-3+4q=12 | | 10x-2(x-3)=8x+2 | | 6-6x=5x-8x-6 | | 3x-18=8x-58 | | 0.10(x+5.00)=2.40 | | (50*45)/60+5=x | | 8m-3-9m=8m-9-3 | | 6x+5+x=1+5x+6 | | 3p-5+7= | | 4r+5r= | | -4(x-2)=-4(x-8)-8x | | 0.10(x+5.00)=2 | | 4x-x+3=2x+18 | | -16t^2+384t+4=1284 | | -4(x-2)=-4(x-8)-8v | | 4x+7-6= | | 11-5x=5x+7-9x | | 3x^2-45x+45=0 | | 12(5+2y)=4y(6-9y) | | 40=10(x+5) | | 40k+70=30k+90 | | -6x+2+7x=14-24 | | -6(3xx-9)=-234 | | 6-2x-1=4+8-6x | | 4-4x=9-9x | | 2(x+4)=3(x-3) | | 1.7t-4.5=7.75 | | 9+3x=2-4x | | 10x+5y=35 | | 6z=3z-8+2z | | (50*45)/60+5= | | 3(4-x)=5+4x |